One Dimensional Shallow Water Equation Streamflow Modeling using WASH123D Model - Basri, H.; M. Sidek, L.; S. Shih, D.; C. Lloyd, H.; H. Azad, W.; Z. Abdul Razad, A. (International Journal of Engineering and Technology, 2018)
Reservoir inflow forecasting assists dam operator in reservoir operation by providing advance information on lake level. This paper discusses on the application of the physical-based numerical model to simulate one-dimensional channel network using WASH123D Model. The model was developed to simulate streamflow at two locations namely Sg Kejar and Sg Tiang, located in the Temengor catchment. The WASH123D model performed channel routing using shallow water equation. The model input data includes rainfall from 5 rainfall stations, river cross sections and simulated runoff data using SCS Method. Due to unavailable observed data, results comparisons were performed using streamflow results obtained using InfoWorks RS Platform. The peak flow from simulation results at Sg Kejar & Sg Tiang Station is 152.6m3/s and 36.6m3/s. The analysis shows good agreement for both simulations with Nash-Sutcliffe Efficiency of 0.68 for Sg Kejar and 0.99 for Sg Tiang. It is suggested that model recalibration shall be made once there is enough water level data to enable more accurate representation of spatial heterogeneity in the catchment processes.Â Â Â